O perfil do paciente diabético tipo 2 atendido em um hospital universitário - OLIVEIRA, Haicha Brarymi (2023)
Introduction: The Diabetes Mellitus type 2 represent one of the kind of this disease. Objective: This study try to analize the epidemic profile of the patients with diabetic mellitus type 2 of the Projeto de Atenção ao Paciente Diabético, on the University Hospital Bettina Ferro de Souza, Belém - Pará, 2007, identifying the prevalence of the sex, the principal treatment and your efficiency in front of glicemy level, the frequent complications personal record linked with this disease. Methods: Realized a individual, descriptive, transversional study basead in a review if the 373 medical prontuaries used a questionnaire research in focus about: age, sex, race, place of born, if the pacient lives in downtown or in rural zone, marital status, profession, study time, antropometric measures, arterial pressure, the time of disease. Results: The totally of 373 patients were the feminine sex. A mean age with most prevalence was around 61 to 70 years. Identified 272 patients with high blood pressure. About the time of disease the most patients had around 10 years with Diabetes Mellitus type 2. 100% of the patients realize some type of treatment, 61,65% used oral drugs to control the glicemy but 253 (67,8%) presented high glicemy levels. The prevalence of the retinophaty was observed in 11% of the cases, neurophaty was 17,7% and dermatophaty only 25,2%. When talk about diabetics personal records, the vascular cerebral accident occur in 10 patients. Conclusion: Today the Diabetes mellitus type 2 is the most prevalent disease with big impact on the mortality due cronics complications resulted of the inefficient public political to informe the health professional and the population this real and serious pathology.